2016
DOI: 10.14238/pi48.6.2008.322-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipids as risk factors in relapsing nephrotic syndrome

Abstract: Background Nephrotic syndrome is primarily a pediatric disorderHyperlipidemia is an important characteristic of nephrotic remission can be found in frequent relapse nephrotic syndrome. Objective To determine plasma lipids as risk factor for relapsing nephrotic syndrome. Methods Thirty children with nephrotic syndrome were included were enrolled as control. Blood specimens were collected to determine phases. Follow up was carried out six months after remission to determine the occurrence of relapsing nephrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The mean age of the study population was 2-6 years which was also correspond to the previous study. 11 In the present study, there was significant rise in total cholesterol, triglycerides, LDL, LDL/HDL ratio, when compared with controls. These findings were similar with the work done by various authors.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The mean age of the study population was 2-6 years which was also correspond to the previous study. 11 In the present study, there was significant rise in total cholesterol, triglycerides, LDL, LDL/HDL ratio, when compared with controls. These findings were similar with the work done by various authors.…”
Section: Discussionsupporting
confidence: 52%
“…9 Lawang SA et al showed that 40% patients had relapse of NS those had highly significant differences in total cholesterol, HDL, LDL, triglyceride and LDL/HDL ratio between acute phase of NS and NS in remission. 10,11 Elevated plasma lipid levels are potential risk factors for atherosclerosis and progression of glomerular injury. Lipidemia may affect the kidneys directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…They were divided into two groups on the basis of lipid profile during remission 16 children developed relapse out of 30 children in group 2 whereas 2 children developed relapse out of 20 children and the difference was statistically significant (0.002). Similar findings observed by Lawang SA et al and Mahmood S et al 19,23 The present study had showed higher value of serum lipid level during remission may be associated with future relapse.…”
Section: Discussionsupporting
confidence: 92%
“…14,15 So, regular close monitoring of lipid profiles is necessary to anticipate complication, especially in frequently relapsing children. 16,17,18,19 Evaluation and treatment of lipid abnormalities are important aspects in the management of NS in children. 20 In NS, more than 95% cases of proteinuria is eliminated by oral prednisolone for few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…So, lipid profile assessment is crucial in children suffering from NS. Persistent hyperlipidemia can lead to a relapse of NS 13 .…”
Section: Introductionmentioning
confidence: 99%